2015
DOI: 10.1155/2015/531485
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in the Utilization of Maternal Healthcare Services in Odisha, India

Abstract: Odisha, one of the socioeconomically disadvantaged states of India, registers high maternal deaths. The state features wide regional and sociodemographic diversity with the Koraput-Balangir-Kalahandi (KBK) districts, dominated by disadvantaged tribal population. This study aims to assess the level and pattern of maternal healthcare services utilization among different subgroups of women in Odisha with a special focus on the regional, economic, and educational inequality using the latest District Level Househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
8
12
0
1
Order By: Relevance
“…For example, in the year 2011, women in the age group 20–29, 30–39 and 40–49 were nearly twice (OR = 1.972(95% CI = 1.220–3.188), (OR = 2.303 (95% CI = 1.352–3.922) and (OR = 2.299 (95% CI = 1.238–4.272) more likely to uptake the skilled delivery care than those in the age group 15–19. This is consistent with the results from other studies [ 7 , 24 , 25 , 26 , 27 ]. The finding that older women in Ethiopia had higher odds of skilled assistance during delivery could be attributed to the better awareness of availability and accessibility of such services.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…For example, in the year 2011, women in the age group 20–29, 30–39 and 40–49 were nearly twice (OR = 1.972(95% CI = 1.220–3.188), (OR = 2.303 (95% CI = 1.352–3.922) and (OR = 2.299 (95% CI = 1.238–4.272) more likely to uptake the skilled delivery care than those in the age group 15–19. This is consistent with the results from other studies [ 7 , 24 , 25 , 26 , 27 ]. The finding that older women in Ethiopia had higher odds of skilled assistance during delivery could be attributed to the better awareness of availability and accessibility of such services.…”
Section: Resultssupporting
confidence: 94%
“…Similar gradient is observed in 2005. Similar finding was also observed in other studies [ 7 , 10 , 15 , 25 , 26 , 28 ]. However, the finding that older aged women have higher odds of uptake of skilled delivery care services and on the other women of higher birth order have lower odds of uptake of such services was surprising since higher birth order women who would generally be older were less likely to seek these services than women of first order birth who would generally be younger.…”
Section: Resultssupporting
confidence: 92%
“…Rural residence in this finding of the study was a hindering factor to the non-use of skilled birth attendants during delivery in Ghana. This finding is consistent with previous studies conducted in India, Sudan and Tanzania [16,19,38] which reported greater use of skilled birth attendants during delivery among urban mothers than rural mothers. This may be due to the fact that women in the rural settlement may not access skilled birth attendants due to lack of health facilities.…”
Section: Discussionsupporting
confidence: 92%
“…Studies conducted in low and middleincome countries show wide gaps in skilled birth delivery. Findings from these studies had shown that wealth, women and husband's educational levels were significantly associated with skilled birth delivery [18][19][20]. For example in Namibia, the concentration index and curve showed that wealth-related inequities were statistically significant in skilled delivery to the benefit of women from economically better-off households.…”
Section: P a G Ementioning
confidence: 99%
“…The present study is the first of its kind which assessed the maternal healthcare service provision from human rights perspective in Odishaan infamous state for its high maternal morbidity and mortality in India. 5,24 The other novelty of this study is that, it included respondents from three differently managed i.e. public, private and public-private partnerships health facilities to have a comparative assessment with reference to their experience during childbirth.…”
Section: Discussionmentioning
confidence: 99%